Smart and fair local energy: Introducing energy local - Barnes, J; Hansen, P; Darby, S (Newcomers, 2021)
To reach the UK’s decarbonisation targets requires radical changes in energy markets as well as the development of new business models and tariffs. The UK has been successful in deploying renewable generation mostly from sun, wind and biomass. Yet, a five-fold increase in deployed renewable generation technologies over the last decade is now concentrating attention on a new challenge: how to make best use of them and keep local distribution networks functioning well. Much innovation effort is being directed towards developing smarter, locally based energy systems. High profile innovation projects grab much of the attention, but below the radar is a range of community-orientated initiatives that are quietly developing alternatives. Energy Local is one such approach, seeking to transform the electricity market for local communities and small-scale generators. By facilitating local sharing of energy, it increases export prices for local generators, reduces electricity costs and fuel poverty for households and keeps money circulating locally. It is pioneering the development and uptake of new tariffs and services that work for consumers, changing people’s thinking on energy and ability to act. Below, we explain how this is done and what the Energy Local approach can contribute to local and national policy goals.